The second coming of Van Gennep among the Serbs A contribution to the history of Serbian ethnology/anthropology in the final quarter of the XX century - Ivan Kovačević (University of Belgrade, 2016)
Emergence of the Serbian translation of Van Gennep’s major work "The Rites of Passage" initiates recapitalization of the influence theory of rites of passage had on studies of customs in Serbian scholarship. It is necessary to make such a review since the Serbian reader of Van Gennep’s book is unaware of that fact. Bibliography of works inspired by Van Gennep in Serbian ethnology/anthropology in the past three decades totals at over 25 books. Influence of Van Gennep’s theory of rites on Serbian ethnology/anthropology is intermediary; it came through British structural anthropology, especially the works of Edmund Lеаch. The interpretation of Serbian ethnographical materials began in the late 1970s and blazed up in the following decade. From then on and until the emergence of Serbian translation in 2005, along with a bit less numerous works of interpretative nature, theoretical volumes also appear transforming and correcting Van Gennep’s theory making it an advanced interpretative means. Application of Van Gennep’s theory of rites of passage to Serbian scholarship was a way of familiarizing with the structural anthropology that was one of the major channels of modernization in the setting of centennial theoretical\methodological backwardness. This modernization was twofold salutary – it prevented the construction of mythology of nationalism at the end of the last century and created an immunity to postmodern mind swamp.